Supportive supervision of routine immunization in Rajnandgaon district of Chhattisgarh - Mendhe, Harshal G. (J Family Med Prim Care, 2019)
BACKGROUND: Immunization coverage in Chhattisgarh has never been abysmal but the improvement is rather insignificant over the years. Some more interventions are essential to strengthen different aspects of immunization services such as micro-planning, cold-chain and logistics management, monitoring/supportive supervision, and community mobilization. The present study was considered as a part of ongoing UNICEF funded Project on Supportive Supervision of Routine Immunization in Rajnandgaon district undertaken by the Department of Community Medicine, Government Medical College, and Rajnandgaon CG with the objectives to observe key quality parameters at Ice Lined Refrigerator (ILR) points and to assess knowledge and practice of Vaccine Cold Chain Handler (VCCH). METHODS: A facility-based, cross-sectional study (repeat survey) was conducted from May 2017 to June 2018 in the Rajnandgaon district of Chhattisgarh. First phase of the study was conducted from May 2017 to November 2017 and repeat survey was conducted from December 2017 to June 2018. Structured questionnaires as a part of standard tool prescribed by Government of India was used for the collection of required data. RESULTS: The cumulative score status out of all the 50 centres in Rajnandgaon district showed improvement in 35 centres. The score of important components such as vaccine management, equipment maintenance, temperature monitoring, and monitoring and supervision information improved, but that of background information and human resource component decreased. CONCLUSION: Supportive supervision strategy can be more beneficial in improving the cold chain maintenance process provided that components such as logistic, infrastructure, and manpower are in place to enhance service delivery. Supportive supervision is a continuous process, so regular follow-up and monitoring visits are essential to achieve the targets.